2021
DOI: 10.3389/fphys.2021.670720
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of an Alternative Weight-Grading Model Against Chronological Age Group Model for the Grouping of Schoolboy Male Rugby Players

Abstract: ObjectivesConcerns regarding marked differences in the weights and body composition of young rugby players competing within the same age groups have led to the suggestion of alternative models for grouping young players. The aims of this study were (1) to compare variance in the body size and body composition of schoolboy rugby players (9 to 14 years), across weight- and age-grading models, and (2) to identify morphotypes for the weight model using Hattori’s body composition chart.Materials and MethodsSkinfold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Overall, 0%−30% of the participants were in the low BDNF group, 30%−70% were in the medium BDNF group, and 70%−100% were in the high BDNF group ( 46 , 47 ). Table 1 shows the basic information of participants in the three BDNF groups and only low and high groups ( N = 58) were used in the following ANOVA and Pearson's chi-square test analysis ( 48 , 49 ).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 0%−30% of the participants were in the low BDNF group, 30%−70% were in the medium BDNF group, and 70%−100% were in the high BDNF group ( 46 , 47 ). Table 1 shows the basic information of participants in the three BDNF groups and only low and high groups ( N = 58) were used in the following ANOVA and Pearson's chi-square test analysis ( 48 , 49 ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the above research and knowledge, classifying youth rugby players by age has become a matter of debate. Whilst age grouping is the most common grouping strategy, several federations have adopted the intuitive method of grouping youth players according to body mass ( see Lentin et al, 2021;Patton et al, 2016). Players with advanced anthropometric characteristics may be ' accelerated' ( i.e., play up) to participate against older players.…”
Section: Grouping Strategiesmentioning
confidence: 99%
“…Conversely, the term ' dispensation' is used for smaller players who are eligible to compete in younger age categories ( i.e., play down) and is considered a strategy that may increase participation ( Cassidy, 2018). Lentin et al ( 2021) showed a weight grading model helped to reduce the variability in body size of young players whilst maintaining the identity of age category in French rugby. However, such a grouping strategy resulted in mainly obese players being ' accelerated' which subsequently resulted in large variability and body composition mismatches.…”
Section: Grouping Strategiesmentioning
confidence: 99%
“…Chronological age and subjective age are considered to be two important concepts and are frequently used as proxies for aging. In the scientific community, chronological age has been generally utilized when dividing individuals into different age groups [ 1 , 2 ]. However, in the gerontology field, chronological age seems to be less important than it is projected to be, especially for the oldest adults.…”
Section: Introductionmentioning
confidence: 99%